UNDERSTANDING TEACHERS’ PROFESSIONAL IDENTITIES THROUGH STORYTELLING WITHIN A POSTCOLONIAL FRAMEWORK - Anwar, Desvalini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
This study provides an account of my doctoral research with respect to the methodological choices that I have made. It focuses on the heuristic value of storytelling for English teachers within a postcolonial setting like Indonesia to construct meanings and understand their experiences ‘consciously within and against accepted forms’ (Miller, 1995, pp. 25-26). It inquires into the finding of ourselves - to understand who we are, who we have been and who we will become for the benefits of the young people in our care. First, I write and construct my autobiographical narrative and then solicit further stories from my teacher interviewees. Our stories allowed us to understand how our professional identities have been influenced and shaped by the social, political, cultural and historical contexts that surround our lives. Placing my study within a postcolonial framework, I was prompted to investigate the ‘heteroglot’ nature (Bakhtin, 1984) of Indonesia as a language community shaped by the history of colonization and the globalization of English. Our stories highlight our efforts to ‘speak back’ to not only our own habitual practices but also to the hierarchical structure of power perpetuated in English. They are not simply told in response to the ‘imagined communities’ of Indonesia as they shape the struggles of those who fought for independence from Dutch rule but are also in conflict with the New Order attempts to impose an ‘official nationalism’ (Anderson, 1991, p. 83) on Indonesians at the expense of any recognition of their regional languages, dialects and cultures. Key words/phrases:  storytelling, professional identities, English teachers, postcolonial framework, habitual practices,